Lipid metabolism dynamics in cancer stem cells: potential targets for cancers - Du, Juan; Qin, Hai (Frontiers in Pharmacology, 2024)
Cancer stem cells (CSCs) represent a small subset of heterogeneous cells within tumors that possess the ability to self-renew and initiate tumorigenesis. They serve as potential drivers for tumor initiation, metastasis, recurrence, and drug resistance. Recent research has demonstrated that the stemness preservation of CSCs is heavily reliant on their unique lipid metabolism alterations, enabling them to maintain their own environmental homeostasis through various mechanisms. The primary objectives involve augmenting intracellular fatty acid (FA) content to bolster energy supply, promoting β-oxidation of FA to optimize energy utilization, and elevating the mevalonate (MVA) pathway for efficient cholesterol synthesis. Additionally, lipid droplets (LDs) can serve as alternative energy sources in the presence of glycolysis blockade in CSCs, thereby safeguarding FA from peroxidation. Furthermore, the interplay between autophagy and lipid metabolism facilitates rapid adaptation of CSCs to the harsh microenvironment induced by chemotherapy. In this review, we comprehensively review recent studies pertaining to lipid metabolism in CSCs and provide a concise overview of the indispensable role played by LDs, FA, cholesterol metabolism, and autophagy in maintaining the stemness of CSCs.